Minimally invasive repair of the severe pectus excavatum in an infant - Muharrem Özkaya; Mehmet Bilgin (Elsevier, 2019)
Pectus excavatum is the most common congenital chest wall abnormality. Nuss et al., in 1998 described minimally invasive repair of pectus excavatum and this procedure is now the procedure of choice in many institutions for the surgical repair of pectus excavatum. However, since that time the optimal age and indications for surgical repair are still debate. Although there is no age limitation for the procedure, publications regarding the surgical management of infants with pectus deformities are few. We present a case of an 11-month-old girl with severe pectus excavatum who presented with a 3-day history of increasing dyspnea which was present since her birth. During her follow in pediatric intensive care unit she became apneic and underwent intubation. A chest tomography demonstrated pectus excavatum with right main stem bronchial compression and bilateral lower lobe pneumonia. She underwent minimally invasive repair of his pectus excavatum and was extubated on hospital day 10 and was discharged from the hospital on postoperative day 17. Keywords: Pectus excavatum, Carinatum, Pediatric